2001
DOI: 10.1042/0264-6021:3580379
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel natriuretic peptide receptor that prefers brain natriuretic peptide over atrial natriuretic peptide

Abstract: Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) exert their physiological actions by binding to natriuretic peptide receptor A (NPRA), a receptor guanylate cyclase (rGC) that synthesizes cGMP in response to both ligands. The family of rGCs is rapidly expanding, and it is plausible that there might be additional, as yet undiscovered, rGCs whose function is to provide alternative signalling pathways for one or both of these peptides, particularly given the low affinity of NPRA for BNP. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
2
24
0
1
Order By: Relevance
“…However, there is evidence that BNP may act locally as an anti-fibrotic factor (Ogawa et al 2001) and that some of the actions of BNP may be mediated by an NPR preferential to BNP over ANF (Goy et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that BNP may act locally as an anti-fibrotic factor (Ogawa et al 2001) and that some of the actions of BNP may be mediated by an NPR preferential to BNP over ANF (Goy et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…(2) Some tissues of GC-A Ϫ/Ϫ mice (ie, the testis and adrenal gland) retain significant high-affinity cGMP responses to BNP. This residual response cannot be accounted for by GC-B or any other known mammalian membrane GC, 59 suggesting that an as-yetunidentified receptor may exist that specifically recognizes BNP.…”
Section: Vascular Effectsmentioning
confidence: 99%
“…Results were standardized per milligram protein, as measured by the Lowry method described previously (12). Guanylyl cyclase activity (basal and BNP stimulated) was measured in membranes isolated from whole hearts (DN-NPRA, n ϭ 4 and WT-NPRA, n ϭ 4 mice) using methods previously described (9). The membrane fractions were divided into four aliquots.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, interpretation of in vivo studies has been confounded by concomitant alterations in load. Furthermore, the density of NPRA receptors on cardiomyocytes is far less than that in lung, kidney, or adrenal tissues (9), raising questions regarding the biological significance of cardiomyocyte NPRA. Holtwick et al (13) reported that mice with cardiac-specific disruption of the NPRA displayed impaired relaxation and an exaggerated hypertrophic response to pressure overload, suggesting that, indeed, cardiomyocyte NPRA modulates cardiac structure and function independently of load.…”
mentioning
confidence: 99%